2009
DOI: 10.1111/j.1600-051x.2009.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of photodynamic therapy in the treatment of periodontitis

Abstract: Application of a single cycle of PDT was not effective as an adjunct to ultrasonic periodontal treatment. There were no extra reductions in pocket depths and bleeding on probing. With regard to eradicating bacteria, however, there are no additional effects as compared with conventional treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
96
6
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 30 publications
12
96
6
19
Order By: Relevance
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers. 22,26,28,31,32 Changes of microbiological parameters were evaluated in 8 of 18 studies.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
See 1 more Smart Citation
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers. 22,26,28,31,32 Changes of microbiological parameters were evaluated in 8 of 18 studies.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…Four studies have found a statistically significant effect of the additional use of PDT on the reduction of periodontal pathogens, 28,35,37,38 while 4 studies have failed to reveal any differences between the treatments groups. 31,33,36,39 Three out of the 18 studies have also evaluated the changes in terms of various inflammatory markers. 29,33,34 All three studies have revealed statistically significantly higher reductions in the investigated inflammatory markers following the additional use of PDT (Table 1).…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…Dessa forma, as três concentrações do azul de toluidina e azul de metileno utilizadas foram 0,05 mg/ml (BERAKDAR et al, 2012;BALATA et al, 2013;PINHEIRO et al, 2010) ,0,1 mg/ml (AL-ZAHRANI et al, 2009;GE et al, 2011;NORO FILHO et al, 2012;THEODORO et al, 2012;BASSIR et al, 2013;FRANCO et al, 2014;MONGARDINI;DI TANNA;PILLONI, 2014) e 10 mg/ml (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;CAPPUYNS et al, 2012;GIANNOPOULOU et al, 2012;NOVAES et al, 2012;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;ARWEILER et al, 2014;BETSY et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;MOREIRA et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;ALWAELI;KHATEEB;AL-SADI, 2015;QUEIROZ et al, 2015). Apesar dos resultados do teste de concentração dos corantes, onde a concentração de 10mg/ml foi a única efetiva para o metileno e a de 5 e 10mg/ml foram as bactericidas para o toluidina, optamos por testar novamente as três concentrações mais comum na literatura acima citada.…”
Section: Discussionunclassified
“…Outros estudos também aplicam essa potência (BRAUN et al, 2008;RÜHLING et al, 2010;GIANNELLI et al, 2012;GIANNOPOULOU et al, 2012;BALATA et al, 2013;DILSIZ;CANAKCI;AYDIN, 2013;ALWAELI;KHATEEB;AL-SADI, 2015). Porém ,outro valor de potência frequentemente encontrado é entre 60 mW e 75 mW (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;BETSY et al, 2014;CHITSAZI et al, 2014;FRANCO et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;QUEIROZ et al, 2015). Por isso optou-se por testar dois valores de potência: 70 e 100 mW.…”
Section: Discussionunclassified
See 1 more Smart Citation